EFFECT OF VITAMIN E AND COD LIVER OIL SUPPLEMENT WITH BIVALENT OIL BASED VACCINE OF NEWCASTLE DISEASE AND INFECTIOUS BRONCHITIS DISEASE ON IMMUNE RESPONSE OF THE BROILERS. - & et al., ABDULWAHID (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was aimed to enhance the immune response of the broilers by vitamin E and Cod liver oil supplement with locally inactivated bivalent vaccine of Newcastle disease and Infectious bronchitis viruses. One hundred and twenty broiler chicks Ross 308 were divided to four groups at 30 chicks of each group. The 2nd group was vaccinated with 0.5ml/chick of locally inactivated ND-IB vaccine at 5 days old. The 3rd group was vaccinated with 0.5ml locally ND-IB vaccine and 0.1 ml/chick of VE. The 4th group was vaccinated with 0.5ml of locally ND-IB vaccine and 0.1ml/chick of Cod liver oil, while the first group was left without vaccination as a control group. All groups were vaccinated with attenuated ND-IB at 3 days old and attenuated IBD at 14 days old. The results of ELISA test revealed that the 3rd and 4th groups showed significantly increased (P≤0.05) in Ab titers against ND virus at aged 35 days, also, the 4th group showed significantly (P≤0.05) increased in Ab titers against IB virus at day 35 of age as compared with the other groups. The 4th group showed a significant (P≤0.05) increased in bursal index as compared with the other groups. The results of challenge test revealed that vaccinated groups resist the velogenic ND and IB viruses with relatively high productive range particularly the 4th group as compared with other groups. In conclusion, the VE and Cod liver oil supplement with local bivalent oil based vaccine of ND and IBV may enhance the immune response of the broilers particularly the 4th group which vaccinated with 0.5 ml of local bivalent oil based vaccine of ND-IB vaccine and 0.1 ml Cod liver oil.